Whose peace are we building? : leadership for peace in Africa. - Mahmoud, Youssef; Albert, Mbiatem (London [England] : I. B. Tauris & Company, Limited, 2021)
"What is the relationship between leadership and peace? What kind of leadership styles, processes and strategies are required to gain a deeper understanding of local context while at the same time maintaining the trust and cooperation of host authorities and other stakeholders on the ground? As concerns mount about the continued relevance and efficiency of UN peace operations, Youssef Mahmoud - who led several challenging peace missions in Africa - draws on many years of experience to offer insights into how political leadership might be exercised to help restore and nurture peace. Mahmoud makes the case for a paradigm shift in the type of leadership required to bring about strong, global diplomacy for peace. Making extensive use of the authors' unique personal experiences in Burundi, Central African Republic and Chad, the book offers an unparalleled insight into the leadership challenges of complex and often seemingly intractable conflict situations."--
Introduction -- 1. Perspectives on Peacebuilding and Leadership -- 2. An Uncharted Leadership Path -- 3. Burundi: A Wounded Puzzle -- 4. Leading BINUB in a Fragile Context -- 5. A Trans-Border Humanitarian Crisis and a Contested Response -- 6. Leading MINURCAT to the Exit Door -- 7. What It Would Take to Build Peace Better? -- Index.
Includes index.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Keywords: Peace-building -- Africa; Conflict management -- Africa; Peace studies & conflict resolution; Africa -- Politics and government -- 21st century; Electronic books